M-Splines baseline hazard approximation for the proportional hazard model with right censored data - Juarez García, Omar Alejandro (2023)
The proportional hazard model plays a fundamental role in the analysis of time-to-event data. In this thesis, we conduct a simulation study to evaluate the performance of M-splines to estimate the baseline cumulative hazard function for the proportional hazard model. We assess the effect of sample size and number of knots in the estimation process. Finally, we apply this method to a sample of students from a university where the event of interest is the payment on time of the last tuition fee.